2006
DOI: 10.1111/j.1440-1673.2006.01623.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally inserted central catheters and upper extremity deep vein thrombosis

Abstract: The purpose of the study was to determine the incidence and risk factors for venous thrombosis in patients with a peripherally inserted central catheter (PICC). A retrospective study of all upper extremity venous duplex scans was carried out in the Vascular Medicine department from year 2000 to 2002 inclusive. A chart review of positive scans was undertaken to identify possible thrombotic risk factors. Of 317 upper extremity venous duplex scans carried out, 115, or 32%, were positive for upper extremity deep v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 18 publications
3
38
0
Order By: Relevance
“…These studies have reported rates between 3 and 7% for symptomatic PRLVT; however, they have not evaluated patients exclusively in the ICU [4,12,13]. This limitation makes the rate of symptomatic PRLVT in the ICU difficult to determine, however, it is likely higher in critically ill patients than in other hospitalized patient populations.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These studies have reported rates between 3 and 7% for symptomatic PRLVT; however, they have not evaluated patients exclusively in the ICU [4,12,13]. This limitation makes the rate of symptomatic PRLVT in the ICU difficult to determine, however, it is likely higher in critically ill patients than in other hospitalized patient populations.…”
Section: Discussionmentioning
confidence: 89%
“…Some authors have suggested PRLVT, whether superficial or deep, is almost entirely asymptomatic [3,5,10,11]. Conversely, a large portion of the existing literature consists of retrospective or prospective observational studies in which thrombosis was identified on imaging studies obtained due to symptoms, most commonly pain, swelling or erythema in the ipsilateral arm [4,6,12,13]. In addition, a recently halted prospective study using routine ultrasound in an ICU patient population demonstrated 20% of patients developed symptomatic PRLVT [7].…”
Section: Introductionmentioning
confidence: 93%
“…[7][8][9]12,14 Few data are available on upper extremity DVT; most of the observational studies have focused on lower extremity DVT. In one study, 11 compared with nonobese patients, obese patients had a 23-fold increase in upper extremity DVT.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of symptomatic PICC-associated UEDVT is small, but due to the large number of PICCs placed each year, they account for up to 35% of all diagnosed UEDVTs [13]. Roughly 1% to 7% of hospitalized patients who undergo PICC placement will develop venous thrombosis; and, the majority of these events will occur after the 14 th day post placement [10,[14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It has being reported that PE complicates UEDVT in 2% to 36% of patients and may occur as the initial clinical presentation of this disorder [5][6][7][8]. Increased use of peripherally inserted central catheters (PICCs) is associated with an elevated risk of UEDVT, particularly in critically ill patients and those with malignancy or receiving chemotherapy [1,4,[9][10][11][12]. The occurrence of symptomatic PICC-associated UEDVT is small, but due to the large number of PICCs placed each year, they account for up to 35% of all diagnosed UEDVTs [13].…”
Section: Introductionmentioning
confidence: 99%